Tratamiento para alopecia androgénica diagnosticada, mediante la aplicación de cóctel de principios activos capilares con la técnica de mesoterapia en paciente masculino de 42 años - Barona Bayas, Melissa Monserrat (2025)
This case study is focused on demonstrating the efficacy of the mesotherapy technique through the application of a cocktail of active hair principles in a 42-year-old male patient diagnosed with male androgenic alopecia (MAGA). The aim of the study was to check the effectiveness of this treatment in halting hair loss and the recovery of the hair follicle, allowing the hair strand to grow and increase the patient's hair density, for which purpose the patient was selected, the diagnosis and initial assessment by means of cosmetological records, followed by the treatment per week, the analysis and evaluation of the results obtained using follow-up records and photographs, and finally the conclusions and recommendations. Hair mesotherapy consists of the infiltration of a cocktail of active ingredients to activate blood microcirculation, thus favouring the nutrition and strengthening of the hair follicle. In this case, panthenol, vitamin B6, vitamin B1, biotin and iron were used, with a frequency of treatment sessions of once a week, for a total of 10 sessions, which, once completed, resulted in an increase in hair density and an evident reduction in hair loss. In summary, the treatment carried out in this case study has demonstrated effectiveness in combating androgenic alopecia, as well as having a positive impact on the patient's quality of life, by recovering their confidence and self-esteem.